2013
DOI: 10.1080/03075079.2013.806460
|View full text |Cite
|
Sign up to set email alerts
|

How the doctorate contributes to the formation of active researchers: what the research tells us

Abstract: While much research focuses on factors contributing to doctoral completion, few studies explore the role of the doctorate in forming active researchers with the skills, knowhow and appetite to pursue research post-completion. This article investigates fifteen existing studies for evidence of what factors in the doctoral experience may contribute to the formation of an active researcher with a capacity for later research productivity. The analysis reveals a productive advisor may be key to forming an active res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 41 publications
(61 reference statements)
0
64
1
1
Order By: Relevance
“…This was reinforced by Brew et al (2011) empirical findings regarding the absence of a relation between high productivity levels and the amount of research development training performed after the PhD. These findings highlight that the dearth of research training opportunities during doctoral studies may not be easily recovered after the completion of the degree (Sinclair et al 2014).…”
Section: Developmental Theory: the Socialization Of Publishing Duringmentioning
confidence: 79%
“…This was reinforced by Brew et al (2011) empirical findings regarding the absence of a relation between high productivity levels and the amount of research development training performed after the PhD. These findings highlight that the dearth of research training opportunities during doctoral studies may not be easily recovered after the completion of the degree (Sinclair et al 2014).…”
Section: Developmental Theory: the Socialization Of Publishing Duringmentioning
confidence: 79%
“…Thus, the citation indexes of the two groups may converge (Long and McGinnis 1981). Sinclair et al (2014) suggested that the productivity of a doctoral candidate's supervisor will influence the productivity of the candidate, and some evidence suggest that the productivity pattern developed at this stage by the candidate will follow him or her later in the academic career.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have argued for increased nuances in the way we consider the impact of doctoral education on different levels of knowledge production (Halse and Mowbray 2011). Others have explored the impact of joint university-industry research on doctoral education (Malfroy 2011) and the role of doctoral education as contributing to the formation of active researchers (Sinclair, Barnacle and Cuthbert 2014).…”
Section: Impact Of the Doctoratementioning
confidence: 99%